Implementing TMCL: XTche: a topic map schema and constraint specification language - Librelotto, Giovani Rubert (2007)
In this paper we present a Topic Maps Validation System – XTche constraint language and its processor. We started with our strong motivation to check a topic map for syntactic and semantic correctness – as a notation to describe an ontology that supports a sophisticated computer system where its validation is crucial! Then we assume XTM and TMCL as starting points and we used our background in compilers and XML validation to come up with our proposal. XTche complies with all requirements stated for TMCL but it is an XML Schema oriented language. This idea brings two benefits: on one hand it allows for the syntactic specification of Topic Maps (not only the constraints), eliminating the need for two separated specifications (schema and constraints); and on the other hand it enables the use of an XML Schema editor (like XMLSpy) to provide a graphical interface and the basic syntactic checker. With XTche,atopicmapdesignerdefinesasetofrestrictionsthatguaranteethataparticulartopicmapissemanticallyvalid.